The Efficacy of Ketamine Administration in Prehospital Pain Management of Trauma Patients; a Systematic Review and Meta-Analysis - Mahmoud Yousefifard; Shaghayegh Askarian-Amiri; Seyedeh Niloufar Rafiei Alavi; Mostafa Sadeghi; Peyman Saberiana; Alireza Baratloo; Mohammad Taghi Talebian (Archives of Academic Emergency Medicine, 2020)
Introduction: Although previous articles and reviews suggest that ketamine might effectively manage pain in trauma patients, these articles have serious limitations. Accordingly, the current meta-analysis aims to investigate the efficacy of ketamine administration in prehospital pain management of trauma patients.